Integrasi Artificial Inteligence (AI) Sebagai Alat Bantu Dalam Penerjemahan Bahasa Arab – Indonesia - Hizam, Ibtisyamah; Aziz , Yek Amin; Hakiki , Ahmad Sirojul (Shaut al Arabiyyah, 2025)
: This research aims to integrate AI as an assistive tool in Arabic translation. The difficulty in translation arises because it requires a deep understanding of various linguistic aspects in both the source and target languages. However, the advent of technology, including Artificial Intelligence (AI), has provided significant ease, particularly in translating Arabic. This tool has increasingly been utilized by language learners as a translation instrument, but its results remain a subject of debate. Issues such as accuracy arise, where the message from the source language may not be fully conveyed to the target language. Conventional translation also cannot be completed quickly because it requires mastery of various subfields of linguistics, such as syntax, lexicology, morphology, semantics, and others. From these challenges, integrating AI as a translation tool presents a potential solution. This study employs a descriptive qualitative method with a literature review approach, focusing on analyzing the translation outputs of AI and professional translators, which are then described. The findings indicate that AI translation demonstrates high accuracy, although some errors persist. However, these errors can be mitigated with professional translation expertise. Thus, it can be concluded that using AI as a translation tool requires prior mastery of translation skills, with AI serving solely as an auxiliary tool that facilitates the translator's work